(untitled) (Journal of Economic Research & Business Administration, 2016)
This article discusses the classical method of speculation in futures contracts. The notion of spread, the effect of the shoulder, arbitration, the principles for calculating the variation margin. Long considered the position and Short on futures contracts in the case of raising and lowering the price of the underlying asset. Presented an example on earning and price divergence actually identical instruments. The notions of contango and backwardation.